Evaluating transportation infrastructure investment on a regional level: a system dynamics simulation. (October 2018) - Wang, Zhong; Zhang, Yingying; Lian, Lian; Chu, Chenglong
Transportation infrastructure investment (TII) has significant influence on regional economic development. This paper aims to measure the potential economic impact of TII and to help policymakers to evaluate different alternatives and strategies at the regional level through a system dynamics (SD) approach. First, an SD model is established to simulate the impact of TII on the economy and employment. The relationship between transportation investments and economic development is examined and the relevant employment and economic indicators are identified. Second, the variables, flow diagrams, and structural equations of the SD model are defined. Third, the program Vensim is employed to establish the SD model with economy, transportation, and employment subsystems. It is then calibrated based on the historical statistics data in Liaoning Province, China. Finally, scenario analysis of different transportation investment plans is presented. The results will help investors, policymakers, and government agencies to estimate the potential outcomes of proposed transportation investment plans and to further develop optimal policies for transportation investment.